Brief Report: Inhibition of miR-145 Enhances Reprogramming of Human Dermal Fibroblasts to Induced Pluripotent Stem Cells. (9th October 2015) - Barta, Tomas; Peskova, Lucie; Collin, Joseph; Montaner, David; Neganova, Irina; Armstrong, Lyle; Lako, Majlinda
Abstract: MicroRNA (miRNAs) are short noncoding RNA molecules involved in many cellular processes and shown to play a key role in somatic cell induced reprogramming. We performed an array based screening to identify candidates that are differentially expressed between dermal skin fibroblasts (DFs) and induced pluripotent stem cells (iPSCs). We focused our investigations on miR-145 and showed that this candidate is highly expressed in DFs relative to iPSCs and significantly downregulated during reprogramming process. Inhibition of miR-145 in DFs led to the induction of "cellular plasticity" demonstrated by: (a) alteration of cell morphology associated with downregulation of mesenchymal and upregulation of epithelial markers; (b) upregulation of pluripotency-associated genes including SOX2, KLF4, C-MYC; (c) downregulation of miRNA let-7b known to inhibit reprogramming; and (iv) increased efficiency of reprogramming to iPSCs in the presence of reprogramming factors. Together, our results indicate a direct functional link between miR-145 and molecular pathways underlying reprogramming of somatic cells to iPSCs.